Bridging the gap: an intergenerational care facility where young and old people are sharing their everyday life - Frykberg, Emma (My University, 2022)
Good health is a combination of physical activity and mental well-being. The World Health Organization defines: “Health as a state of complete physical, mental and social well-being”. With increasing age, physical activity decreases. Residents in residential care facilities in Sweden rarely achieve the general recommendations for their daily activities. Social isolation is another problem individuals encounter when growing older. Mental illness is a widespread problem in Sweden and the loneliest are the people above 75 years old. Mental illness is more common for residents at residential care facilities than among people who live in ordinary accommodation. Through architecture, the concept of combining different generations will be developed, and hopefully, inspire society to deal with today’s issues of the aging population. This Master Thesis investigates how young children and old people can make use of each other and in what way the connection between the generations can contribute to better health. The study will be conducted through literature studies, and interviews with different target groups combined with professions in the field of healthcare and architecture. The report will analyze examples of existing intergenerational programs and adapt them to a concept that can be implemented in a design of a building. The result of the theoretical studies will be implemented in a design proposal with a focus on the social benefits of a building where children and older people are sharing their everyday life together. This Master Thesis will hopefully open the question and discussion about how our society is taking care of our elderly.
Keywords: Intergenerational programs, Mental health, Physical activity; Residential care, Childcare, Healthcare Architecture